Cuckoo song - Hardinge, Frances (Amulet Books, 2015)
In post-World War I England, eleven-year-old Triss nearly drowns in a millpond known as "The Grimmer" and emerges with memory gaps, aware that something is terribly wrong, and to try to set things right, she must meet a twisted architect who has designs on her family.